2017
DOI: 10.4067/s0718-95162017000300003
|View full text |Cite
|
Sign up to set email alerts
|

Possible use of struvite as an alternative phosphate fertilizer

Abstract: Struvite, from human urine, is an alternative phosphorus (P) fertilizer. This study evaluated P release from struvite and its effectiveness for maize in Inanda (Ia), Sepane (Se) and Cartref (Cf) soils. Phosphorus sorption isotherms were determined, an incubation study determined the release pattern of P from struvite, and a pot trial compared struvite with single superphosphate (SSP) on maize P uptake. The amount of P at equilibrium (where Q = 0) in the Cf was 1.39 mg L , respectively. The extractable P in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The result of the greater purity of the ECST material was numerically greater concentrations of total P (22.8%) and total N (9.3%) than for CPST (11.3 and 5.5%, respectively; Table 1). Although several studies have reported struvite containing in the range of 12–14% total P (Johnston & Richards, 2003; Kataki et al., 2016; Liu et al., 2012; Nongqwenga et al., 2017; Rahman et al., 2014), the greater total P concentration in the ECST material used in this study is still within the 11–26% total P range reported for struvite (Johnston & Richards, 2003; Kataki et al., 2016). In addition, the ECST material used in this study also had a numerically lower Mg concentration (5.7%) than that of CPST (8.0%; Table 1), although this was likely related to the differential recovery processes and is common among struvite sources.…”
Section: Results An Discussionsupporting
confidence: 50%
“…The result of the greater purity of the ECST material was numerically greater concentrations of total P (22.8%) and total N (9.3%) than for CPST (11.3 and 5.5%, respectively; Table 1). Although several studies have reported struvite containing in the range of 12–14% total P (Johnston & Richards, 2003; Kataki et al., 2016; Liu et al., 2012; Nongqwenga et al., 2017; Rahman et al., 2014), the greater total P concentration in the ECST material used in this study is still within the 11–26% total P range reported for struvite (Johnston & Richards, 2003; Kataki et al., 2016). In addition, the ECST material used in this study also had a numerically lower Mg concentration (5.7%) than that of CPST (8.0%; Table 1), although this was likely related to the differential recovery processes and is common among struvite sources.…”
Section: Results An Discussionsupporting
confidence: 50%
“…The M3‐P concentration had increased from the initial concentration in the SiCL soil for both the 0.5‐ and 1‐mo sampling, but the M3‐P concentration did not differ from the initial concentration after the soil was saturated and flooded (Figure 6a). The differences in the trends of M3‐P concentration changes among the three soils were likely related to the greater initial clay content, OM, and Fe concentrations in the SiCL than in the other two SiL soils that could bind P, which would have allowed M3‐P to persist longer in the two SiL soils (Nongqwenga et al., 2017). The change in M3‐K concentrations differed independently among soils and differed over time ( p < .05; Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Amorphous calcium phosphate ACP appeared in solid phase. The final product represents thus a mix of both these phosphates, what is not, however, essential drawback in practical application of such product in agriculture as a valuable mineral fertilizer slowly dosing its nutrient content [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Composition of impurities observed in liquid manure influenced also struvite crystal shape disadvantageously (compare Figure 1a and 1b). In general, quality of the product manufactured from liquid manure CLM should be regarded as unsatisfactory in respect to market demands [27,28]. Improvement of the product quality is, however, possible, among others, through elongation of residence time of struvite suspension in a crystallizer [15,16,24].…”
Section: G(l) Kinetic Model Corresponding Analytical N(l) Form [26]mentioning
confidence: 99%